INCORPORATING MASS MEDIA TO BUILD LEARNERS’ LANGUAGE SKILLS IN AN AUTHENTIC AND ENGAGING MANNER (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This paper explores the pedagogical benefits of utilizing authentic television series for English language acquisition. We present a methodology emphasizing active viewing strategies, including the strategic use of subtitles for enhanced listening comprehension, mimicry and repetition for improved pronunciation, and mindful engagement with cultural nuances embedded within the narrative. The approach advocates for targeted vocabulary acquisition, focusing on contextual understanding and regular review to ensure retention. Furthermore, the paper highlights the importance of creating an engaging classroom environment that mirrors the enjoyable experience of watching series independently, emphasizing the iterative process of analyzing teaching methods and adapting strategies for optimal learning outcomes.